2013
DOI: 10.1016/j.ophtha.2012.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Attributes Associated with Eye Care Use in the United States: A Meta-Analysis

Abstract: Objective To model the factors that are associated with the use of eye care services among the United States population with and without diabetes, stratifying by age group. Design Meta-analysis. Participants We analyzed data from three datasets: the Behavioral Risk Factors Surveillance System combined years 2006-2009, the National Health and Nutrition Examination Survey combined years 2005-2008, and the National Health Interview Survey year 2008. For all three datasets, we analyzed data from all survey par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
44
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 17 publications
7
44
1
Order By: Relevance
“…In contrast to earlier studies, 14, 31, 37, 38 we found little positive effect of educational attainment and income on regular receipt of eye exams. The reasons could be that educational attainment and income work through other channels, including higher cognitive function, better health, better awareness of signs and symptoms of poor health, and more comprehensive health insurance coverage, all of which were explicitly measured in this study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to earlier studies, 14, 31, 37, 38 we found little positive effect of educational attainment and income on regular receipt of eye exams. The reasons could be that educational attainment and income work through other channels, including higher cognitive function, better health, better awareness of signs and symptoms of poor health, and more comprehensive health insurance coverage, all of which were explicitly measured in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…This result, although unexpected, is not out of line with the current literature as several studies have shown that black race is a statistically significant predictor of eye care use among persons aged 40 – 64 but not 65 or older. 30, 31 Educational attainment primarily made a difference to receipt of eye exams during follow-up in our univariate analysis.…”
Section: Discussionmentioning
confidence: 95%
“…Eye-care usage rates were low in our study, with only 24.7% of diabetic individuals with visual aids attending yearly eye checks. This is much lower than that of the USA, where a meta-analysis15 in 2013 showed that annual eye-care rates ranged from 64% to 72%. Another surprising finding in our study was that 78.1% of those who were aware of their visual deterioration had undiagnosed DR, and were likely not accessing eye-care services.…”
Section: Discussionmentioning
confidence: 77%
“…Even in the United States, annual use of eye services was significantly associated with levels of educational attainment after adjusting for other factors. [32][33][34] A randomized controlled trial demonstrated that educational interventions can successfully increase the uptake of cataract surgery. 35 Sex differences in the health burden of cataract vision loss were significant for each age group.…”
Section: Discussionmentioning
confidence: 99%